2018
DOI: 10.1016/j.cemconcomp.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary Portland Cement composition for the optimization of the synergies of supplementary cementitious materials of ternary binders in hydration processes

Abstract: The synergistic effects of using several supplementary cementitious materials (SCMs), such as Blast Furnace Slags plus Limestone Filler or Fly Ashes, depend on the OPC composition. When using an OPC which is poor in C 3 A and alkalis in ternary formulations, a similar initial strength gain to that of a plain OPC is detected and at longer hydration ages, the formation of monocarboaluminate, hemicarbonate and hydrotalcite instead of monosulphate can be seen. If an OPC with a higher C 3 A content and alkalis is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…mixed with BFS and FA resulted in 32-59% lower compressive strength than for the plain PC after 7 days of hydration. In contrast, Menéndez et al (15) saw that ternary blends using PC with 2% C 3 A, LF and BFS showed better strength than binary blends and similar than plain PC during hydration from 1 to 90 days, which were attributed to the LF at early ages and to the BFS hydration at long term (11,15,21). The good mechanical strength of the ternary blends at long term has been also related to the refinement of the pore structure (21-23) which has a further positive response on durability (26).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…mixed with BFS and FA resulted in 32-59% lower compressive strength than for the plain PC after 7 days of hydration. In contrast, Menéndez et al (15) saw that ternary blends using PC with 2% C 3 A, LF and BFS showed better strength than binary blends and similar than plain PC during hydration from 1 to 90 days, which were attributed to the LF at early ages and to the BFS hydration at long term (11,15,21). The good mechanical strength of the ternary blends at long term has been also related to the refinement of the pore structure (21-23) which has a further positive response on durability (26).…”
Section: Introductionmentioning
confidence: 85%
“…The good mechanical strength of the ternary blends at long term has been also related to the refinement of the pore structure (21-23) which has a further positive response on durability (26). Besides, present authors in a previous paper (21) found that ternary blends with high blended content formed more C-S-H that contained more Al and less C/S ratio than C-S-H gels formed with plain PC and retained more alkalis in their structure.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations